Analisa Kebutuhan dan Pengelolaan Parkir Secara Terpadu Kawasan Heritage Kayutangan Malang - Ahdat, Sergius Kurniawan; Yurnalisdel, Yurnalisdel; Rahma, Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Parking is very important, especially in popular tourist locations. As tourism develops in the Kayutangan Heritage area of Malang, two- and four-wheeled vehicles are often seen on the shoulder of Basuki Rahmat road from Radjabali T-junction to JPU. The purpose of this study is to plan the parking space for two and four-wheeled cars in the Kayutangan Heritage Area of Malang. Two different types of data are required for this research, namely: Information Sources: Talks, Notes, and Eyewitness Accounts. The list of potential parking spaces from the Ministry of Transportation is secondary information. The largest car parking peak occurred on Saturday, August 12, 2023 based on data collected from Thursday, August 10 to Wednesday, August 16, 2023. Based on the calculation of parking space requirements for two- and four-wheeled vehicles. There are more cars coming. There are plenty of parking spaces, and there is an area of 288 m² (18 mx 16 m) designated for two-wheelers. This gives us 192 parking spaces, but not enough two-wheelers to handle the approaching cars; according to research, 296 spaces are needed. For the incoming cars, a parking lot will be built on the second floor. So, we have 384 spaces, or 288 m2 x 2 = 576 m², which is enough to fit one car. There are 64 four-wheeler parking spaces, each measuring 46 by 21 meters or 966 square meters. The result shows that 63 parking spaces are needed to accommodate the incoming cars.